Ecoturismo e interpretação da paisagem no Alto Camaquã/RS: uma alternativa para o (des)envolvimento local - Degrandi, Simone Marafiga (2011)
The fast development of tourism as a worldwide intensity, starting from the 1970s, has resulted in social, economic and environmental problems. As a consequence, in this same period, the environmental movement while condemning the touristic activity reflected on alternatives that would provide the reduction of impacts. Thus new standards began in the forms of visiting nature, with the the emergence of various forms of alternative tourism, which acted as a counterpoint to the predatory practices of mass tourism. In this context, Ecotourism emerged as a major form of contact with nature and appreciation of the environment. Ecotourism is configured as a type of tourism that is growing globally each year, having as main feature the use of natural heritage in a sustainable way, seeking their protection through awareness, interpretation and environmental education, including further socio-cultural aspects, focused particularly in the appreciation of local cultures visited. The use of natural potential as a tourist attraction, added to cultural aspects of the host communities, has emerged as a major tool for endogenous development of territories that have rich potential landscape. From this trend, this paper has proposed a survey to study the potential of the natural aspects linked to the geological and geomorphological heritage of the Alto Camaquã, for the development of ecotourism as a tool for endogenous regional development and public policies for landscape protection . The Alto Camaquã is located in the southern half of the state of Rio Grande do Sul, in the upper third of Camaquã River Basin, located between the region of Campanha and the Mountains of the Southeast. This research was methodologically based on the geosystems approach for the interpretation of the landscape of Alto Camaquã, through the identification of landscape units. Thus, we identified the main points of actual interest for the development of ecotourism and the potential of this landscape to create a Geopark. At the end we can conclude that among the landscape units established during the research, highlights the great diversity of landforms and rock outcrops, mainly found in the Sub-região Natural Planaltos Rebaixados de Caçapava do Sul that need to be protected, such , the watchtowers, the Mines of Camaquã, the Secret Stone, the Corner of Hell, the Stone House, among other places. Besides these there are other formations that add to the geological and geomorphological heritage and have particular potential for the development of future projects related to routing Ecotourism and cultural diversity of the Alto Camaquã